2008
DOI: 10.1080/01446190701749151
|View full text |Cite
|
Sign up to set email alerts
|

Volume building as competitive strategy

Abstract: The competitive strategy and advantage of building contractors is examined. In Hong Kong, just a few contractors have dominated the market of public housing construction, where prefabrication is mandatory. Does prefabrication technology lead to business success? Based on quantitative analysis of a questionnaire survey and its validation with interviews, we find that prefabrication by itself is not regarded as a sustainable source of competitive advantage. Instead, market share is the most statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…It is suggested that firms work together through systematic coordination and proper communication in long-term alliances (Khanna et al, 1998). This enhances the supply chain to deliver better construction services through a trust-building process (Chiang et al, 2008 Firms that avoid making changes to their processes (C 8 ) are also likely to be more profitable (r ¼ 0.321, p ¼ 0.022). This may be because unchecked changes can lead to extra cost thereby reducing profits.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that firms work together through systematic coordination and proper communication in long-term alliances (Khanna et al, 1998). This enhances the supply chain to deliver better construction services through a trust-building process (Chiang et al, 2008 Firms that avoid making changes to their processes (C 8 ) are also likely to be more profitable (r ¼ 0.321, p ¼ 0.022). This may be because unchecked changes can lead to extra cost thereby reducing profits.…”
Section: Discussionmentioning
confidence: 99%
“…Care should be taken when interpreting the results in the context of housebuilding in some other countries where the linkages between contracting and housebuilding are much closer and the decoupling of housebuilding from land acquisition in new housing development is generally much clearer (Meikle 2008). This point is illustrated by the primary business strategy adopted in housebuilding elsewhere, for example, mass customization through innovation in production in Japan (Barlow and Ozaki 2005), volume house building based on cost leadership in Hong Kong (Chiang et al 2008), and supply-contractor integration for modular house-building in the Netherlands (Hofman et al 2009). Also, Ball (2008), drawing on an international comparison, concluded that UK housebuilding has a much higher degree of concentration than either Australia or the US, and attributed that to land planning dominance and market diversification of large firms in the UK.…”
Section: Different Countriesmentioning
confidence: 99%
“…Vertical linkages offer possibilities for various subcontractors to work together through systematic coordination and proper communication in long-term alliances (Khanna et al, 1998). Enhancing the supply chain to deliver better construction services through a trust-building process is suggested by Chiang et al (2008) to achieve competitiveness.…”
Section: Cost Leadershipmentioning
confidence: 99%
“…Investment in new equipment and machines to accommodate the local technological level is necessary to ensure that the benefits from a foreign firm's advanced technology can be applied in the host country. Chiang et al (2008) proposed that advanced technology allows a foreign firm to handle projects of a larger scale, thereby enabling it to take advantage of the economies of scale. Being better equipped with advanced information management systems, which include building design, business administration, project management and communications, means there can be more efficient and effective information exchange within the organization, thus enhancing productivity (Shen et al, 2006).…”
Section: Cost Leadershipmentioning
confidence: 99%